FARNESYL DIPHOSPHATE SYNTHASE (FDRS) AND GERANYLGERANYL DIPHOSPHATE SYNTHASE (GGSP1) GENE POLYMORPHISMS AND EFFICIENCY OF THERAPY WITH BISPHOSPHONATES IN RUSSIAN WOMEN WITH POSTMENOPAUSAL OSTEOPOROSIS: A PILOT STUDY - M. Yu. Krylov; O. A. Nikitinskaya; E. Yu. Samarkina; N. V. Demin; N. V. Toroptsova (Научно-практическая ревматология)
Genetic factors that are an important hereditary component determining a predisposition to osteoporosis (OP) are 60–80% responsible for bone mineral density (BMD). Some polymorphic genes have been previously shown to affect the efficiency of performed anti-osteoporotic therapy.Objective: to study the impact of farnesyl diphosphate synthase (FDRS) and geranylgeranyl diphosphate synthase (GGSPI) gene polymorphisms on BMD changes during 12-month therapy with bisphosphonates (BP) in women with postmenopausal OP.Subjects and methods. The investigation enrolled 53 women with OP. Spine and proximal femur BMD was determined using X-ray densitometry before and after BP treatment. The -99A/C and -8188T ins/del polymorphisms in the FDPS and GGPS1 genes were investigated using real-time polymerase chain reaction.Results and discussion. The BMD changes were less marked in women with the C allele of C/T -99/C polymorphism in the FDPS gene than those in carriers of the genotype AA: 2.3±3.6 and 4.4±3.8% (р = 0.062) in the spine; 0.6±3.1 and 2.8±4.5% (р = 0.075) in the femoral neck; 0.5±2.9 and 2.5±2.8% (р = 0.020) in the entire femur, respectively. Femoral neck densitometry showed a significantly weaker response to BP treatment in the patients carrying the mutant genotype del/del of GGSP1 -8188T ins/del polymorphism than in those with the wild-type genotype ins/ins (0.8±4.2 and 4.1±2.5%, respectively; р = 0.030). No significant differences for this polymorphism were found in other areas of BMD measurement.Conclusion. The described pilot study has indicated that the examined FDPS and GGSP1 gene polymorphisms may be predictors for a response to BP therapy in patients with OP. Further investigations that will contribute to the choice of the most effective therapy for this disease are needed to confirm our results.